Comparison of the effects of two pre-synchronization protocols (g6g and pg-3-g) on some reproductive performance parameters in holstein cows - Metehan Kutlu; Dursun Ali Dinç (Eurasian Journal of Veterinary Sciences)
Aim: The present study was aimed to determine effects of G6G and PG-3-G presynchronization protocols on some reproductive parameters in Holstein cows between postpartum 28-40 days. Materials and Methods: Cows in the G6G group (n=35) were treated with PGF2α on day (d) 0, GnRH on days 2 and 8, and PGF2α on day 15. The injection of last GnRH was applied 56 hours after the second PGF2α injection and then timed artifical insemination (TAI) was performed 16-18 hours later. Cows in the PG-3-G group (n=35) were treated with PGF2α on day 0, GnRH on day 3 and 10, and PGF2? on day 17. The injection of last GnRH and TAI were applied as they were done for G6G group. Results: There were no statistical differences between the G6G and PG-3-G groups in terms of submission rate (100% and 100%), the first-service pregnancy per artificial insemination (P/AI) (42.9% and 51.4%), calving to first insemination interval (53.5 and 54.0 d), calving to conception interval (54.1 and 53.7 d), calving interval (334.1 and 333.7 d) were determined. When the data analyzed according to the protocol at the beginning of cows to be "cyclic" and "noncyclic", P/AI were found to be 64.7% and 41.5%, respectively. The difference between the groups was tended to be significant (p=0.098). Conclusion: Start of presynchronization protocols in the early postpartum period, provides 100% SR after the voluntary waiting period. It is clearly shown that the presynchronization protocols reduces the calving interval less than 400 days. Time and labor cost could be saved as there would be no needs for oestrus detection and appropriate P/AI could also be achieved in non-cyclic cows.